Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Cuidado em território de exclusão social: covid-19 expõe marcas coloniais - Camilo, Claudia; Kahhale, Edna; Ferreira, Maria Luísa; Schveitzer, Mariana (Saúde e Sociedade, 2021)
A intersecção de gênero, raça e classe marca os territórios de exclusão social, especialmente em um país que carrega cicatrizes da colonialidade patriarcal e capitalista em suas estruturas, como é o caso do Brasil. O objetivo deste trabalho é compreender o cuidado em um desses territórios: a cidade de Cubatão/SP. A investigação, feita entre 2017 e 2020, incluiu a pandemia da covid-19, que sobrecarregou o cuidado no território. O método foi a pesquisa qualitativa, com oficinas, observação participante e entrevistas de profundidade. O cuidado era majoritariamente oferecido por mulheres, líderes comunitárias e profissionais da atenção primária do Sistema Único de Saúde. Para analisar os dados, utilizou-se a hermenêutica de profundidade. O referencial teórico foi a costura das teorias feministas da ética do cuidado, ecofeministas e interseccionais. A pesquisa revelou diversos desafios e potencialidades, como o cuidado ético-político, eixo da busca por justiça socioambiental. , Abstract The intersection of gender, race and class marks the territories of social exclusion, especially in a country that carries scars of a patriarchal and capitalist colonialism in its structures, as is the case in Brazil. The objective was to understand care in this territory of exclusion in Cubatão, São Paulo, Brazil. The research, conducted between 2017 and 2020, included the pandemic of COVID-19, which overloaded care in this territory. The method was qualitative research, with workshops, participant observation and in-depth interviews. The care delivered by community leaders and primary health care professionals from the Brazilian National Health System was mostly performed by women. For data analysis, depth hermeneutics was used. The theoretical reference was the perspective of feminists: ecofeminist, intersectional and Care Ethics. The study showed several challenges and the ethical-political care as an axis in the search for social and environmental justice.
http://www.scielo.br/scielo.php?script=sci_arttext&pid=S0104-12902021000200202&tlng=pt
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; brésil; care; covid-19; intersectionnalité; pandémie; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; travail; écoféminisme

Hidden in plain sight: Uncovering the emotional labor of Black women students at historically White colleges and universities. - Kelly, Bridget T.; Gardner, Paige J.; Stone, Joakina; Hixson, Ashley; Dissassa, Di-Tu (Journal of Diversity in Higher Education, 2021)
We utilized the emotional labor triangle to understand how 16 Black women students who attended Historically white colleges and universities (HWCUs) navigated gendered-racialized oppressive environments that mattered to their academic success. This study contributes to a gap in the literature, as much of the research focused on students of color without disaggregating for gender or other social identities. In addition, the literature is scant on experiences of Black women students use of emotional labor. Emotional labor has largely been studied from a management perspective. Through qualitative semi-structured interviews, we examined the emotional labor Black women expended while pursuing their undergraduate degree. We employed a qualitative, intersectional, methodological approach to foreground historically marginalized voices and situated the study in the hypervisibility Black women participants described feeling as space invaders on their historically White undergraduate campus and at the same time the invisibleness of their voice and masking of their feelings as they encountered gendered racism. Further, we emphasized the emotional toll and stress that may occur for Black women when they do not utilize engaged coping mechanisms while expending their emotional labor. The study holds implications for educators to address emotional labor inequities within HWCUs. (PsycInfo Database Record (c) 2021 APA, all rights reserved) © 2019 National Association of Diversity Officers in Higher Education
Number: 2
Keywords: amériques; approches et analyses; care; colère; femmes universitaires noires*; intersectionnalité; projet charge mentale; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail émotionnel; violences; états-unis

Kuei, je te salue: conversation sur le racisme - Béchard, Deni Ellis; Kanapé Fontaine, Natasha (Éditions Écosociété, 2020)
« En 2016, la poète lnnu Natasha Kanapé Fontaine et le romancier québéco-américain Deni Ellis Béchard entamaient une conversation sans tabou sur le racisme entre Autochtones et Allochtones. Comment cohabiter si notre histoire commune est empreinte de honte, de blessures et de colère? Comment faire réaliser aux Blancs le privilège invisible de la domination historique? Comment guérir les Autochtones des stigmates du génocide culturel? Ces questions traversent leurs échanges: Natasha raconte sa découverte des pensionnats autochtones, son obsession pour la crise d'Oka, la vie dans la communauté de Pessamit ; Deni parle du racisme ordinaire de son père, de la ségrégation envers les Afro-Américains, de son identité de Québécois aux États-Unis. Cinq ans plus tard, Deni et Natasha reprennent la plume pour poursuivre ce "rendez-vous de la parole qui s'ouvre". Renouant avec le ton intimiste et le foisonnement intellectuel de leur premier échange, ils abordent des sujets d'une brûlante actualité: mobilisation de Black Lives Matter après la mort de George Floyd, feux de forêt en Californie, campagne présidentielle sur fond de montée de l'intolérance; soulèvement des Wet'suwet'en et blocus ferroviaires, dénonciation de la politique de la reconnaissance du gouvernement Trudeau. Puis survient l'impensable: Joyce Echaquan, une Atikamekw de 37 ans, meurt sous les injures racistes de deux infirmières de l'hôpital de Joliette. Une vague d'indignation monte ...»–Quatrième de couverture.
Section: 203 pages ; 22 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; santé; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires

Là où je me terre: roman - Dawson, Caroline (Les éditions du remue-ménage, 2020)
« Valparaíso, décembre 1986, tremblement de terre entre les quatre murs d'une maison. Un homme et une femme annoncent à leurs enfants qu'il faut tout laisser derrière et fuir le Chili de Pinochet. C'est Noël, la petite Caroline a sept ans et elle aura la nausée durant tout le voyage. La fillette atterrit à Montréal. En plus de la neige dehors, il y a le tapis rouge vin de l'hôtel Ramada qui accueille les personnes réfugiées en attente de papiers. Il y a aussi Passe-Partout qui semble s'adresser à elle à travers le téléviseur. Après le premier appartement à Montréal-Nord, la classe d'accueil de madame Thérèse qui lui apprend le français, les enfants qui se moquent de ses cheveux et de sa boîte à lunch, la misère des rues d'Hochelaga, il y aura tout ce temps passé dans les banques où ses parents font des ménages. Entre l'exil, les fantômes du passé et le jeu des différences, la petite Caroline camouflera sa furieuse envie de vivre pour ne plus détonner et devenir une immigrante modèle. Mais comment apprend-on à ne plus s'effacer? Peut-on embrasser une nouvelle culture sans renier ses origines? Lumineux et vivant, Là où je me terre sonde la possibilité d'aimer et de lutter sans ne plus avoir à fuir. »
Section: 201 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; intersectionnalité; inégalités; justice sociale; lit301N; littérature; maternité; montréal; premier cycle; périodes historiques; québec; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; écriture des femmes*